2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Kuhn, Jens H; Adkins, Scott; Alkhovsky, Sergey V; Avšič-Županc, Tatjana; Ayllón, María A; Bahl, Justin; Balkema-Buschmann, Anne; Ballinger, Matthew J; Bandte, Martina; Beer, Martin; Bejerman, Nicolas; Bergeron, Éric; et al. (Archives of virology, 2022)
In March 2022, following the annual International Committee on Taxonomy of Viruses (ICTV) ratification vote on newly proposed taxa, the phylum Negarnaviricota was amended and emended. The phylum was expanded by two new families (bunyaviral Discoviridae and Tulasviridae), 41 new genera, and 98 new species. Three hundred forty-nine species were renamed and/or moved. The accidentally misspelled names of seven species were corrected. This article presents the updated taxonomy of Negarnaviricota as now accepted by the ICTV.
Keywords: viry; Mononegavirales; Humans; Phylogeny; fylogeneze; Viruses; lidé